Exploring the awareness and challenges faced by basic stage teachers in integrating nanotechnology into education in Jordan - Ahmad , Fadi Bani (Journal of Education and e-Learning Research, 2026)
This study aimed to explore the levels of awareness of nanotechnology among primary school teachers in Jordan and to identify the challenges hindering its integration into educational practices. To achieve this aim, the researcher adopted a descriptive research design and developed a carefully structured questionnaire based on a review of previous studies, which was validated by experts and distributed electronically to the participants. Data were collected from a sample of 100 teachers in Amman. The analysis revealed that teachers possess a relatively high level of awareness and demonstrate strong positive attitudes toward adopting nanotechnology in classroom teaching. This advanced level of awareness can be attributed to the nature of the “digital age,” in which rapid technological developments and the abundant flow of information through digital platforms enhance teachers’ knowledge of emerging sciences, making them more receptive to technological innovations such as nanotechnology. Despite this theoretical awareness, the study identified a practical implementation gap due to significant challenges, including logistical constraints, limited access to advanced resources and teaching tools, and the lack of specialized training programs that translate theoretical knowledge into tangible classroom practice. Accordingly, the study recommends the development of a national framework incorporating hands-on workshops and the provision of necessary resources. Establishing the infrastructure for practical application could serve as a cornerstone to ensure that primary education aligns with the demands of the Fourth Industrial Revolution, effectively transforming digital awareness into applied, practical learning experiences.